Alterações no uso do solo e seus impactos na simulação de componentes hidrológicos numa bacia hidrográfica agrícola de clima subtropical - Lima, Edberto Moura (2022)
Land use and land cover (LULC) changes are one of the main driving forces of Global Change, shaping the landscape and impacting nature`s contribution to people, including water-related services. Different types of land use and their management practices influence hydrology at both field and catchment scales. Therefore, understanding the dynamic of LULC and their effect on the hydrological components are vital to mitigate their impacts on the natural ecosystem and water resources. Here, we investigated the spatial and temporal dynamics of the Guaporé watershed (2,490 km²), southern Brazil, and their effect on water resources. For a better understanding, the study was divided into three chapters. First, the spatial and temporal differences in land-use distribution were computed by applying landscape metrics. Then, an autocorrelation analysis was used to identify trends in the land-use changes, followed by building up a cellular automata model to assess the main drivers of land use. Finally, we simulated the response of hydrological processes to LULC changes with the Soil & Water Assessment Tool (SWAT). The overall results showed that the land use has dramatically changed in the Guaporé watershed. Most of the changes were explained at the local level by social and economic factors, where the intensification of agricultural activity has promoted homogenization and reduced landscape complexity. These observed changes highlighted the importance to consider a dynamic land-use to assess water resources. Although both static and dynamic scenarios produced a “satisfactory” simulation of historical discharge, an analysis based on a single baseline map could result in an unrealistic representation of water balance since different land-use types imply changes in water infiltration, runoff, plant canopy, among others. Finally, our results highlighted that controlling LULC change is essential for long-term water management quantifying water resources.